Psychometric Properties of the Arabic Version of the Addiction Severity Index (ASI-5): A Cross-Cultural Validation Study in Egypt and Saudi Arabia - Abouzed M; Aljadani A; Gabr A; Elsheikh M; Almuqahwi MS; Alrashidy MF; Alrashidi GK; Soliman MF; Altamimi AN; Alenze NS; Elsaadouni N (Substance Abuse and Rehabilitation)
Mohamed Abouzed,1 Ahmed Aljadani,2 Amgad Gabr,1 Mohamed Elsheikh,1 Mohamed Saad Almuqahwi,3 Mohamed Fayed Alrashidy,4 Ghali Khalaf Alrashidi,4 Mahmoud Farag Soliman,5 Amal Nasser Altamimi,4 Nida Saleh Alenze,4 Nisrin Elsaadouni6 1Psychiatry Department, Faculty of Medicine, Al-Azhar University, Cairo, Egypt; 2College of Medicine, University of Ha’il, Ha’il, Saudi Arabia; 3Erada Mental Hospital, Dammam, Saudi Arabia; 4Erada Mental Hospital, Ha’il, Saudi Arabia; 5Psychiatry Department, Faculty of Medicine, Ain Shams University, Cairo, Egypt; 6Psychiatry Department, Faculty of Medicine, Mansoura University, Mansoura, EgyptCorrespondence: Mohamed Abouzed, Psychiatry Department, Faculty of Medicine, Al-Azhar University, Cairo, Egypt, Email dr_m.abozeid@azhar.edu.egBackground: The Addiction Severity Index (ASI) is a globally recognized tool for assessing substance use disorder (SUD) severity. Despite its widespread use, no validated Arabic version exists. This study aimed to validate the Arabic ASI-5 in Egypt and Saudi Arabia and evaluate its psychometric properties.Methods: : A cross-sectional study recruited 400 participants (200 per country) from inpatient/outpatient SUD treatment centers. The ASI-5 underwent forward-backward translation, pilot testing, and cultural adaptation. Internal consistency (Cronbach’s α), test-retest reliability (Spearman’s ρ), and inter-observer reliability were assessed. Convergent and discriminant validity were evaluated using adjusted Spearman’s correlations.Results: The Arabic ASI-5 demonstrated acceptable internal consistency (α = 0.61– 0.82), with medical (α = 0.78) and psychiatric (α = 0.82) domains showing the highest reliability. Lower consistency in drug (α = 0.62) and legal (α = 0.61) domains reflected cultural and methodological factors. Test-retest (ρ = 0.55– 0.98) and inter-observer reliability (ρ = 0.78– 0.99) were strong. Convergent validity was robust for medical and psychiatric domains (r = 0.70– 0.85).Conclusion: The Arabic ASI-5 is a reliable tool for assessing SUD severity in Arabic-speaking populations. Further refinement of drug and legal domains is recommended to enhance cultural relevance.Keywords: addiction severity index, substance use disorder, cross-cultural validation, psychometrics